D O C U M E N T 2 5 5 A U G U S T 1 9 2 8 2 4 9 This now proceeds as follows:[4] Apart from sign changes for the index 4, we are dealing here with the—only in the first approximation coupled—equations: (1) , and this time, we take generally: (2) without summation over . (1) We then w[ithout] l[oss] o[f] g[enerality][5] integrate them, obtaining (3) , always summing over For , we find in particular (3*) , so that (3) can now be written as: (3 * ) naturally, (3*) + (3 * ) is equivalent to (3). We now take in general: (4) (3*) and (3 * ) are now converted to: (4*) (4 * ) We will denote the symmetric part of as , the nonsymmetric as . Our equations then become (5) (5*) and thus also, by combination: (5 * ) (5) and (5*) complete the problem. Now I set: (6) (therefore harmonic) from which h v v h vv h v v – h v v – + 0 = h v H () v 2 x x ---------------- = v H H v – H H v – + vv 0 = = H H v – vv 0 = H v H v – H v H – + vv 0 = H () () H () () w/o sum. H a + = H w/o sum. 0 = H v vv 0 = H v H v – H + vv 0 = H () H + vv 0 = H H U H v U v + vv H v U v – vv 0 = = H w/o summ. U = = H v H v – H U v U v – U + + + vv = H v H v – H U v – U v U – + + vv 0 = = H vv 0 = H vv 0 = 2U v 2U v – U + vv 0 = U vv v H vv v H = =